Employment Effects of the Earned Income Tax Credit: Taking the Long View - Diane Whitmore Schanzenbach; Michael R. Strain (Institute of Labor Economics (IZA), 2020)
The Earned Income Tax Credit (EITC) is the cornerstone U.S. anti-poverty program, typically lifting over 5 million children out of poverty each year. Targeted to low-income households with children, and only available to those who work, the EITC contains strong incentives for non-workers to become employed. Most of the existing economics literature focuses on federal EITC expansions in the 1980s and 1990s. This paper takes a longer view, studying all federal expansions since the program's inception in 1975. We find robust evidence that EITC expansions increase the extensive margin of labor supply.
Keywords: J22; J28; H31; I38; 330; earned income tax credit; EITC; labor supply